Directorate for Educational Baghdad (Karkh second) Death and the Barzakh in the Qur’an to Canadian Orientalist Leor Halevi in his book The Tomb of Muhamma (Journal of the College of Basic Education, 2024)
Death and the grave in the Holy Qur’an are among the rare topics in research and study. The important thing is that the grave represents the first stage of the transition from this world to the afterlife. Therefore, the Orientalists studied this stage in their writings. The most prominent of these writings is what the Canadian Orientalist Leor Halevi wrote in his book (Muhammad's Grave). Which presented extensive research and a real study of the opinions of scholars about the grave in Islam. In this topic, I dealt with the research entitled (Death and the Barzakh in the Qur’an according to the Canadian orientalist Leor Halevi in his book Muhammad's Grave - Presentation and Analysis) which studies the views of the orientalist Lior Halevy about death and the barzakh, criticizing his statements. And his phrases contained in the book Muhammad's Grave.